2017
DOI: 10.18038/aubtda.339963
|View full text |Cite
|
Sign up to set email alerts
|

Functional Composite Nanofibers Derived From Natural Extract of Satureja Hortensis

Abstract: Development of environmentally friendly and natural-based products with healing properties has become a popular trend for human health. Here, for the first time as far as known, we reported an efficient antibacterial composite nanofiber which was functionalized with the herbal extract of Satureja hortensis (SH) via electrospinning technique for wound care dressing applications. The plant which was used for this purpose is cultivated on a commercial scale in our country, Turkey, and it is relatively inexpensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…4 a, the graph shows the main characteristic bands for PVDF at 840 cm −1 for CH 2 rocking, C–C and CF 2 stretching, 1175 and 1400 cm −1 for C-F, and C-H vibrations, respectively 43 45 . While the characteristic bands of TPU appeared at 1533, 1735, 2971, 3365 cm −1 corresponding to –CONH– asymmetrical bond, C=O, C–H, and N–H stretching, respectively 46 , 47 . The resultant data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 a, the graph shows the main characteristic bands for PVDF at 840 cm −1 for CH 2 rocking, C–C and CF 2 stretching, 1175 and 1400 cm −1 for C-F, and C-H vibrations, respectively 43 45 . While the characteristic bands of TPU appeared at 1533, 1735, 2971, 3365 cm −1 corresponding to –CONH– asymmetrical bond, C=O, C–H, and N–H stretching, respectively 46 , 47 . The resultant data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As seen the barrier effect of TPU to release SH extract to the environment was higher than that of SEBS in the case for S. aureus , therefore SEBS composite nanofibers demonstrated higher antibacterial activity. In addition to that, in our previous studies, we have observed different interactions between a variety of polymers and plants extracts in which we applied plants extract to indicate as natural antibacterial agents in order to use in biomedical applications …”
Section: Resultsmentioning
confidence: 87%
“…The first aim of this study was to obtain nanofibers by the electrospinning technique from the SEBS triblock copolymer and functionalize these fibers with natural agents. In line with this goal, the Satureja hortensis ( SH ) plant extract, which has bioactive properties against Gram‐negative and Gram‐positive pathogens was used as a natural agent . As a result, antibacterial SEBS triblock copolymer composite nanofiber mats were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…5 , the characteristic bands of PVDF appeared at 840 cm −1 corresponding to the rocking of CH 2 , C–C, and CF 2 stretching, in addition to 1175 cm −1 for C–F and 1400 cm −1 for C–H vibrations 78 80 . Nevertheless, the main characteristic bands for TPU were observed at 3365, 2971, 1735, and 1533 cm −1 , corresponding to N–H stretching, C–H, C = O, and CONH– asymmetrical bond, respectively 81 , 82 . The β-phase fraction was calculated as shown in Table 1 , through the following equation:
Figure 5 FT-IR analysis of PVDF and PVDF/TPU (85:15) nanofibers.
…”
Section: Resultsmentioning
confidence: 98%